If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 12 = 3(t + 5) Reorder the terms: 12 + 5t = 3(t + 5) Reorder the terms: 12 + 5t = 3(5 + t) 12 + 5t = (5 * 3 + t * 3) 12 + 5t = (15 + 3t) Solving 12 + 5t = 15 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 12 + 5t + -3t = 15 + 3t + -3t Combine like terms: 5t + -3t = 2t 12 + 2t = 15 + 3t + -3t Combine like terms: 3t + -3t = 0 12 + 2t = 15 + 0 12 + 2t = 15 Add '-12' to each side of the equation. 12 + -12 + 2t = 15 + -12 Combine like terms: 12 + -12 = 0 0 + 2t = 15 + -12 2t = 15 + -12 Combine like terms: 15 + -12 = 3 2t = 3 Divide each side by '2'. t = 1.5 Simplifying t = 1.5
| 9a+11=29 | | 55x-3(9x+12)=64 | | -4/9(2x-4)=48 | | 5(3x+2)=55 | | 3y-4=5y+3 | | 3(x-4)(x+2)=2(x^2+2x+2)+x(x-3) | | -12+3=0 | | 81t^3-25t=0 | | x*2-x-49=6 | | (x-6)(2x+2)=(x+6)(x-2) | | 4(x+1)=4x+3 | | 2x^2+15x+18= | | 5x-8x-12-6=0 | | x*2-x-22=5 | | x*2-x-9=4 | | x*2-x-3=3 | | 2/3+15=17 | | x*2-x-0.5=2 | | z^2-36z=0 | | 2y+5=27 | | 1.5h(48)=634.40 | | 7(y+4)=2y-17 | | X-1+3x=15 | | 7x-2=4x+7 | | ln(5-6x)= | | 8h-2/9=6 | | 31x-16-19x=4(3x-5)+4 | | 15+3x=45 | | r^2-10r-750=0 | | 1x+1=-7x+9 | | 2(7-h)=-12 | | 1.5h+40(48)=634.40 |